Evidence of Amine–CO2 Interactions in Two Pillared‐Layer MOFs Probed by X‐ray Crystallography1. Issue 19 (20th March 2015) - Hu, Xiao‐Li; Gong, Qi‐Han; Zhong, Rong‐Lin; Wang, Xin‐Long; Qin, Chao; Wang, Hao; Li, Jing; Shao, Kui‐Zhan; Su, Zhong‐Min
Abstract: Two pillared‐layer metal–organic frameworks (MOFs; PMOF‐55 and NH2 ‐PMOF‐55) based on 1, 2, 4‐triazole and terephthalic acid (bdc)/NH2 ‐bdc ligands were assembled and display framework stabilities, to a certain degree, in both acid/alkaline solutions and toward water. They exhibit high CO2 uptakes and selective CO2 /N2 adsorption capacities, with CO2 /N2 selectivity in the range of 24–27, as calculated by the ideal adsorbed solution theory method. More remarkably, the site and interactions between the host network and the CO2 molecules were investigated by single‐crystal X‐ray diffraction, which showed that the main interaction between the CO2 molecules and PMOF‐55 is due to multipoint supramolecular interactions of CH⋅⋅⋅O, C⋅⋅⋅O, and O⋅⋅⋅O. Amino functional groups were shown to enhance the CO2 adsorption and identified as strong adsorption sites for CO2 by X‐ray crystallography. Abstract : Selective MOFs : Two pillared‐layer metal–organic frameworks were assembled and shown to display both framework stability and selective CO2 adsorption. The selectivities were evaluated from three independent methods, that is, single‐component gas‐adsorption isotherms, binary gas‐adsorption studies by the ideal adsorbed solution theory method, and crystallographic determination of the adsorbed gas. The results further demonstrated amine–CO2 interactions at a molecular level.